Flavobacterium humi sp. nov., a flexirubin-type pigment producing bacterium, isolated from soil - Kim, Inhyup; Kim, Jiyoun; Chhetri, Geeta; Seo, Taegun (The journal of microbiology, 2019)
A yellow pigmented, Gram-stain-negative, strictly aerobic, rod-shaped, motile by means of gliding, catalase and oxidase positive bacterium, designated strain DS2-A T , was isolated from soil. Growth was observed at 4–32°C (optimum, 28°C), pH 6–9 (optimum, 7.0), and with 0–0.25% (w/v) NaCl (optimum, 0%). Phylogenetic analysis of 16S rRNA gene sequence revealed that strain DS2-A T belonged to the genus Flavobacterium and was most closely related to Flavobacterium aquatile LMG 4008 T (96.4%), Flavobacterium terrae DSM 18829 T (95.6%), Flavobacterium vireti THG-SM1 T (95.5%), Flavobacterium inkyongense IMCC27201 T (95.4%), Flavobacterium brevivitae TTM-43 T (95.2%), and Flavobacterium cucumis DSM 18830 T (95.2%). Strain DS2-A T produces flexirubin-type pigments. The major fatty acids were iso-C 15:0 , iso-C 17:0 3-OH, and iso-C 15:0 3-OH. The major respiratory quinone was identified as menaquinone-6. The major polar lipid was found to be phosphatidylethanolamine. The average nucleotide identity values between strain DS2-A T and selected taxa, F. aquatile LMG 4008 T , F. terrae DSM 18829 T , and F. cucumis DSM 18830 T , were 72, 72.7, and 71.6%, respectively. The draft genome of strain DS2-A T has a number of 14 contigs, scaffold N50 of 476,310 bp and a total size of 3,563,867 bp. Additionally, strain DS2-A T contains 3,127 of gene, 41 of tRNA, 6 of rRNA, and 3 of ncRNA. The DNA G + C content of stain DS2-A T was 40.7 mol%. Based on phylogenetic and phenotypic analyses, strain DS2-A T is considered as a novel species of the genus Flavobacterium , for which the name Flavobacterium humi sp. nov., (type strain DS2-A T = KACC 19715 T = JCM 32786 T ) has been proposed.